Karyological study of Ololygon tripui (Lourenço, Nascimento and Pires, 2009), (Anura, Hylidae) with comments on chromosomal traits among populations - Peixoto, Marco Antônio A.; Oliveira, Marina P. C.; Feio, Renato N.; Dergam, Jorge A. (Comparative Cytogenetics, 2016)
To increase the number of cytogenetic characters used in Ololygon tripui systematics, we applied some cytogenetic techniques such as Giemsa, C- and NOR-banding, and fluorescence in situ hybridization (FISH) with 18S rDNA and repetitive microsatellite DNA probes to the study of four populations from Minas Gerais State (southeastern Brazil). All populations showed 2n = 24 and FN = 48, and chromosomal formula 8m + 10sm + 6st. Nucleolar organizing regions (NORs) were located on chromosome pair 6 in all populations, although in the Tripuí locality additional markings were observed on one homologue of chromosome pair 3. These patterns were partially congruent with results obtained using the 18S rDNA FISH probe. The microsatellites repetitive DNA (GA) 15 and (CAT) 10 probes accumulated predominantly in the terminal region of all chromosomes. Chromosome morphology and Ag-NOR were conserved among populations, a conserved pattern in Ololygon Fitzinger, 1843. Repetitive DNA FISH probes patterns were similar among populations, but they revealed species-specific differences when compared with other species of the genus Ololygon, suggesting that molecular cytogenetics are potentially more informative in karyologically conservative taxa.
Keywords: Cytotaxonomy; Population cytogenetics; Ag-NOR; Heterochromatic blocks; 18S rDNA; FISH; Micros- atellite DNA probes